Carbon based copper(II) phthalocyanine catalysts for electrochemical CO2 reduction: Effect of carbon support on electrocatalytic activity. (30th October 2020) - Latiff, Naziah Mohamad; Fu, Xiaoxu; Mohamed, Dara Khairunnisa; Veksha, Andrei; Handayani, Murni; Lisak, Grzegorz
Abstract: Carbon-metal hybrid materials have shown promising performance as electrocatalysts for CO2 reduction. Here, a comparative study of how different carbons supports influence this reaction is presented. The tested carbon supports were graphene oxide, multi-walled carbon nanotubes, carbon black and activated carbon while the metal complex selected was copper(II) phthalocyanine (CuPc). The CuPc supported on carbon nanotubes (CNT) and carbon black were found to give higher faradaic efficiencies (FE) for reduced carbon products, i.e. 66.3% and 81.8%, respectively compared to graphene oxide (0.0%) and activated carbon (12.8%). Amongst various sizes of CNT, long and thin tubes (in the range of 10–30 nm diameter size, 10–30 μm length) demonstrated higher FE (66.3%) relative to shorter and thicker ones (7.4%). Additionally, the novel use of CNT synthesized from post-consumer plastic waste was also explored as a potential carbon support material. It demonstrated comparable performance to commercial CNT in terms of FE (70.4%). Graphical abstract: Image 1 Highlights: Carbon nanotubes (CNTs) and carbon black were found superior for CO2 reduction. Long (10–30 μm) and thin (10–30 nm Ø) CNTs provided better faradaic efficiency. The plastic waste derived CNTs were successfully applied as carbon support. Waste derived CNTs resulted in comparable faradaic efficiencies to commercial CNTs.